1995
DOI: 10.1017/s0031182000081075
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental factors on the infectivity ofEchinococcus multiloculariseggs

Abstract: The sensitivity of eggs of Echinococcus multilocularis to environmental and controlled laboratory conditions was tested. Egg material was exposed and the infectivity was subsequently monitored by in vitro activation and by oral infection of the natural host, Microtus arvalis. To study the impact of environmental conditions in an endemic area of south-western Germany, eggs were sealed into bags of nylon mesh and exposed to the natural climate during various seasons. The maximal survival time of eggs was 240 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
186
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(206 citation statements)
references
References 14 publications
(9 reference statements)
6
186
0
14
Order By: Relevance
“…In the present work, only one of 58 tissue samples was unfertile. This lesion was probably too young (from 1.5 mo to 3 mo are necessary for the appearance of protoscoleces; Marchiondo and Andersen, 1984;Veit et al, 1995). This would suggest that O. zibethicus is a very effective intermediate host for E. multilocularis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, only one of 58 tissue samples was unfertile. This lesion was probably too young (from 1.5 mo to 3 mo are necessary for the appearance of protoscoleces; Marchiondo and Andersen, 1984;Veit et al, 1995). This would suggest that O. zibethicus is a very effective intermediate host for E. multilocularis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key factors is probably the altitude: E. multilocularis is a parasite that originates from cold regions (Hanosset et al, 2004). Indeed, the eggs of E. multilocularis have a survival time higher in cold temperatures (Veit et al, 1995). Delattre et al (1991) showed that alveolar echinococcosis is more prevalent in regions with cold temperatures and a relative humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Echinococcus eggs are extremely resistant enabling them to withstand a wide range of environmental temperatures for many months (Gemmell et al, 1986 ½Q11 ; Schantz et al, 1995;Thevenet et al, 2005;Veit et al, 1995). Dessication is lethal and the end points for temperature are approximately þ40 C to À70 C (Gemmell and Roberts, 1995).…”
Section: U N C O R R E C T E D P R O O F P0170mentioning
confidence: 99%
“…The samples were stored at −80°C for 72 h to kill Echinococcus spp. eggs [30] and promote the safety of the researchers. This parasite has recently been found in coyotes in Calgary [31][32][33][34], and therefore this precaution was determined to be necessary.…”
Section: Faecal Sampling Protocolmentioning
confidence: 99%